Ensino-aprendizagem de aspectos da língua portuguesa para surdos com experiência acadêmica: um estudo à luz da pesquisa crítica de colaboração - Freitas, Maly Magalhaes [UNIFESP] (2020)
This research aimed to investigate the possibilities for teaching and learning grammatical aspects of Portuguese by deaf people who already have experience with this language. For this purpose, a distance learning course based on material available to listeners was developed for deaf students with some contents related to the Portuguese Language Orthographic Agreement. For the pilot project implementation, four deaf learners participated. This project was divided into two stages, named as Stage I and Stage II, in order to evaluate the methodological aspects, the didactic resources and the accessibility of the referred course. It is based on Vygotsky’s socio-cultural-historical theory (1924-1934), on studies on the teaching of Brazilian Sign Language (Libras) as L1 (QUADROS, 2000) to deaf students (KARNOPP; PEREIRA, 2015; MÜLLER, 2016) and on second language teaching methodologies. This study is inserted in the Critical Collaborative Research since it is based on the negotiation of meanings, which allows reflection and transformation of the participants. People who participated in Stage I revealed that: (1) the use of Brazilian Sign Language Alphabet without the meaning expressed in Brazilian Sign Language or image can make it difficult for deaf people with little lexical knowledge to comprehend; (2) signing exact Portuguese is not Libras, so it does not facilitate learning; and (3) the lack of context for using the studied grammatical rule makes it difficult to understand the content. Thus, for Stage II, one of the course modules was reformulated, covering these suggestions and taking into account the concept of language as interactional and dialogical. The students redid this module and noticed a significant change in the visual and contextual aspects of the grammatical teaching developed in Libras, attending the specificities of the deaf students. The professor-researcher studied new didactic and methodological possibilities for the course and, in this process, there was a transformation of her pedagogical practices.